The routes to exile : France and the Spanish Civil War refugees, 1939-2009 - Soo, Scott (Studies in modern French history., 2013)
As they trudged over the Pyrenees, the Spanish republicans became one of the most iconoclastic groups of refugees to have sought refuge in twentieth-century France. This book explores the array of opportunities, constraints, choices and motivations that characterised their lives. Using a wide range of empirical material, it presents a compelling case for rethinking exile in relation to refugees' lived experiences and memory activities.